Language and the Thing in Itself in the fiction of John Banville - Payne, Jessica Raechel (Rhodes University, Faculty of Humanities, Department of Literary Studies in English)
This thesis consists of an exploration of the interaction between language and the thing in itself in the fiction of John Banville. The thing in itself is that which exceeds the text and to which it cannot refer, even as it is compelled to do so. In exploring this tension, the thesis focuses on how Banville's writing, in foregrounding the inadequacy of the literary text, makes the reader aware of the existence of what exceeds it. Each of the chapters in the study examines the various strategies through which Banville gestures beyond the text in spite of the limitations placed upon him by form and genre. The first chapter studies the tendency in this writer's texts to view death as an apotheosis of the soul in which the individual finally has access to the thing in itself, which they had previously encountered as infants before entering language. The second chapter examines how elements of Romantic thought, such as nostalgia, the seniority of the child over the adult and a particular impression of the natural world, contribute to Banville's attempt to gesture towards the thing in itself. In the third chapter, the role of language in distorting one's understanding of the other is examined. The final chapter of the thesis examines the narrative strategies (including mise en abyme, ekphrasis, metaphor and catachresis) Banville uses in order to present the reader with excess. Ultimately, this study suggests that Banville uses various narrative strategies to make his reader aware of that which exists outside of the text. By gesturing beyond the novel to the sublime, and by self-reflexively exposing the inner workings of the writing process to the reader, Banville's texts confront the reader with an intimation of ineluctable excess.
Keywords: Banville, John -- Criticism and interpretation; English literature -- 20th century -- History and criticism; Language and languages in literature; Narrative inquiry (Research method); Hermeneutics; Excess (Philosophy); Literary criticism